Efektivitas Pemanenan Mikroalga (Spirulina platensis) dengan Metode Elektrokoagulasi menggunakan Tegangan yang Berbeda - Aidil Fadli Ilhamdy; Ginanjar Pratama; Jumsurizal Jumsurizal; Raja Marwita Sari Putri; Darma Saputra (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2021)
Research on laboratory scale Spirulina platensis cultivation in Indonesia has developed quite a lot, however, several obstacles occur at harvest time, ranging from high prices and a very long time. Therefore this study aims to determine the effectiveness of the use of electrocoagulation in harvesting S. platensis using different voltage. The research phase included microalgae cultivation, electrocoagulation process, and harvesting of S. platensis, then continued with an analysis of biomass S. platensis, proximate composition, and water quality (pH, temperature, and Ferro (Fe) content). The treatment of electrocoagulation method harvesting of microalgae with voltages 0, 5, 10, and 15 volts (F0, F1, F2, and F3, respectively) were applied in this study. The best biomass harvested with electrocoagulation from F3 treatment was 6.05 gr/L. The proximate content of S. platensis with F0, F1, F2, and F3 treatments were moisture 24.58%, 12.32%, 15.36%, 17.8%, ash 26.56%, 22.42%, 26.53%, 34.99%, protein 34.24%, 30.26%, 25.81%, 21.67%, fat 1.27%, 0.86%, 1.65%, 0.65%, and carbohydrate 13.35%, 34.15%, 30.66%, 25.22%, respectively. The water quality result showed with, F0, F1, F2, and F3 treatments were pH 7, 7, 9, 8, temperature 32°C, 32°C, 32°C, 34°C, Ferro (Fe) 0.1 mg/L, 8.01 mg/L, 12.58 mg/L, 12.29 mg/L, respectively. The best treatment with electrocoagulation method harvesting was F3.